(untitled) (Asian Journal of Pharmaceutics (AJP), 2014)
The objective of the present study is to prepare, characterize, and evaluate starch phosphate as a carrier in solid dispersions for enhancing the dissolution rate of irbesartan (IRB). The feasibility of formulating solid dispersions of IRB in starch phosphate into compressed tablets with enhanced dissolution rate was also investigated. Starch phosphate prepared by reacting starch with di‑sodium hydrogen orthophosphate anhydrous at elevated temperatures was insoluble in water and has good swelling (400%) property without pasting or gelling when heated in water. Solid dispersions of IRB in starch phosphate prepared by solvent evaporation method employing various weight ratios of drug: Starch phosphate gave rapid and higher dissolution of IRB when compared to pure drug. The 19.92‑ and 39.98‑fold increase in the dissolution rate (K1) of IRB was observed with solid dispersions ISD4 and ISD5, respectively. The dissolution efficiency up to 30 min (DE30) was also increased from 10.58% in the case of IRB pure drug to 81.77% and 88.28% in the case of ISD4 and ISD5, respectively. IRB tablets formulated employing its solid dispersions in starch phosphate also gave rapid and higher dissolution rate and DE30 when compared to plain and commercial tablets. The 33.82‑ and 59.66‑fold increase in the dissolution rate (K1) was observed with formulations IBTF2 and IBTF3 when compared to formulation IBTF1. Starch phosphate could be used as a carrier to enhance the dissolution rate of IRB from its solid dispersions as well as tablet formulations. Key words: Irbesartan, solid dispersions, starch phosphate, tablets and modified starches